14-18 - Goudaillier, Jean-Pierre (Linguistica (Ljubljana), 2018)
This study is part of a series of research studies relating to the terms and expressions that French soldiers used at the front during the period 1914-1918. In World War I, the first large-scale mechanised war, intensive use of previously known as well as new weapons took place. To these weapons, as well as to other death machines of the time, correspond both old designations and neologisms used by the soldeirs. In this article, the names of military devices are presented along with the trems referring to injuries caused by them.
Keywords: argo; francoščina; neologizmi; svetovna vojna 1914-1918; vojaško besedišče; vojni besednjak